Agroecology in the Limousin Mountains: Relocating and Diversifying Food Production to Encourage Employment and Conserve Semi-Natural Spaces - Nathan Morsel; Nadège Garambois (Revue de Géographie Alpine)
In the 1950s, the Limousin Mountain region was characterized by mixed crop and livestock farming, produced mainly for local consumption. Over the past 70 years, however, this small area of the Massif Central has since specialized in breeding cattle for export, breaking the link between agriculture and the local food system. At the same time, physical labor productivity has continued to grow, leading to the massive abandonment of the moors and peat bogs, the region’s pastoral ecosystems. In contrast to these dynamics, for nearly ten years a small group of farmers has been developing agroecological systems, putting native vegetation at the center of feeding their herds. While these systems address agroecological and food transition concerns, they are affected by the industry’s normal standards, which are not adapted to their products. The farmers have therefore had to turn to short supply chains and more local outlets. Local markets nevertheless have their limits and encourage a closer collaboration between breeders and butchers as well as reflection on the stakes of food equity in declining rural areas like the Limousin Mountains.